Marine fishes in the Black Sea: recent conservation status - YANKOVA, M. H.; PAVLOV, D.; IVANOVA, P.; KARPOVA, E.; BOLTACHEV, A.; ÖZTÜRK, B.; BAT, L.; ORAL, M.; MGELADZE, M. (Mediterranean Marine Science, 2014)
A revised checklist of the fish fauna of the Black Sea is reported. This paper is the first attempt to present an actual Check List of the fishes in the Black Sea according to the data available in the Black Sea countries, as well as their current conservation status, enlisted in IUCN. The total number of the Black Sea fish species is 189. Concerning the conservation status only two species (1.06 %) are extinct (Acipenser nudiventris and A. sturio), 3.70 % are critically endangered, 16.40 % are vulnerable, 1.06% are endangered, for 10.58 % there is a lack of data, 26.46% has been classified in the category “Least concern”, 2.65 % are “Near threatened” and 38. 10% are “Not evaluated”.